Pengaruh Penerapan PSAK 71, BOPO dan NPL Terhadap Profitabilitas Pada Perbankan yang Terdaftar di BEI - Gine Das Prena; Sri Kesuma Dewi Nareswari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
The objective of current study was to investigate the influence of Allowance for Impairment Losses (CKPN), Operating Costs on Operating Income (BOPO) and Non-Performing Loans (NPL) on profitability in banks listed on IDX. The new policy standard which was effective in early 2021, the enactment of PSAK 71 which calculates CKPN using a new method as well as an increase in the BOPO and NPL ratios that affect bank profitability. There are 47 banking populations, using purposive sampling with criteria so that the number of samples is 40 banks from Q1 2020 to Q2 2021. The data source used is a secondary data source with a quantitative approach in the form of documentation techniques by collecting financial reports which are accessed through www.idx.co.id, www.ojk.go.id, or the website of each bank. Data was analyzed by using SPSS through multiple linear regression analysis approach. Empirical results thorugh partial analysis show that CKPN, BOPO and NPL each have a negative influence on profitability in banks. Furthermore, the results of the F test show that CKPN, BOPO and NPL both have a negative influence on banking profitability in banks